Children’s trust in print: what is the impact of late exposure to reading instruction? - Einav, Shiri; Rydland, Veslemøy; Grøver, Vibeke; Robinson, Elizabeth J.; Harris, Paul L. (Wiley, 2018)
Prior research in England has indicated that, unlike pre-readers, young children who have learned to decode simple words view print-based information as a more authoritative source of knowledge than purely oral information. We predicted that children in Norway – who start to receive formal reading instruction at a relatively late age – would be slower to display this bias toward print-based information. Accordingly, we tested 4-6 year-olds (N = 96) in Norway. As expected, these children showed a delayed emergence of the bias toward print over speech. Unexpectedly, however, children who had successfully gained a basic reading ability prior to any exposure to formal reading instruction in school were no more trusting of print than their pre-reading peers. These results suggest that the ability to decode simple words is an important condition for selective trust in print-based information but that exposure to formal reading instruction in school may also be necessary.